'With agroecology, we can defend ourselves': examining campesino resilience and economic solidarity during pandemic-era economic shock in Guatemala. Issue 2 (7th February 2023) - Rice, Anika M.; Einbinder, Nathan; Calderón, Claudia Irene
ABSTRACT: The global spread of Covid-19 led to travel and market restrictions that impacted Guatemala's rural food systems. This distinct economic shock directly affected campesinos, or small-scale farmers who depend on subsistence and commercial food production. Some Guatemalan farmer organizations have been promoting agroecology for decades in efforts to strengthen rural livelihoods and food sovereignty, defend Indigenous rights, and adapt to climate change, and agroecology is positioned as a tool for resilience to various shocks. We consider the neoliberal cooptation of the concept of resilience, and its usefulness in preserving alternative and previous (Indigenous) practices. Data from surveys and semi-structured interviews with farmers and leaders at eight organizations that promote agroecology suggests that prior engagement with a farmer organization, enacted through both agroecological practices and social networks, contributes to campesino resilience to the pandemic's economic shock at the farm level, with regards to production and consumption. This study illustrates the range and diversity of strategies taken up by campesinos during the pandemic, and considers the importance of social networks for collective actions that increase current and future economic solidarity in campesino communities.